The Use of QR Code-Based Arabic Ewan Textbooks in Learning Mahārah Kalām - Salamah, Ummu; Wibisono, Muassomah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Learning Arabic for beginners Of course, you really need a guide book in learning a language. The book does not seem archaic and monotonous but a textbook that is creative, innovative and easy to understand for students. Al Maahira IIBS Malang, recently this institution launched the implementation of a very interesting textbook adopted from Ewan University, namely the book "Ewan Arabic" in which there are Arabic language materials juxtaposed with QR Codes. This will help teachers in developing their teaching innovations, even making the teaching process more exciting creative to support the student learning process to run smoothly and foster the spirit of student learning motivation. The researcher used a qualitative descriptive method supported by quantitative data analysis. The use of QR-Code-based ewan textbooks supports students in learning maharah kalam can motivate them. The learning atmosphere has changed to be more lively students are also more active and enthusiastic.